Bridging incremental to transformative hazard management strategies on the Tule River Indian Reservation - Natalie Herbert; Caroline Beckman; Kerri Vera; Eric Coles; Thomas Kim; Seung-Hyun Cho; Gabrielle Wong-Parodi (Environmental Research: Health)
Compounding hazards are becoming more common due to global environmental change. To build societal resilience, there is a need to focus on how people are made vulnerable by our social, political, and economic systems that turn hazards into disasters. Incremental adaptation, often piecemeal and hazard-specific actions, will be insufficient for keeping pace with the rapid global environmental changes already underway. Instead, transformative adaptation is necessary for meeting this need, although the pathways for how to create transformative as opposed to incremental change through individual action and social systems are challenging. These challenges for climate adaptation are on display in rural American Indian Tribal Nations, including the Tule River Indian Reservation, the site of this co-produced research. The Reservation is rural and isolated, and many of the 2000 members manage chronic health conditions like diabetes alongside increasing wildfire and wildfire smoke, extreme heat, drought, and flooding hazards. We ask: how do emergency managers and health practitioners on the Reservation characterize hazards and the vulnerabilities of the people they serve, and how do these understandings determine viable pathways for adaptation to support community health? We interviewed 16 practitioners with expertise in emergency management and health care services on the Tule River Indian Reservation. Using a grounded theory approach to analyze practitioner interviews, our article makes two major contributions. First, we identify a conceptual framework by which practitioners connect people to each other and to place, from place to compounding hazards, and from vulnerabilities to hazard management strategies. Second, our conceptual framework illustrates the incremental-transformative adaptation tension. Most adaptation strategies under consideration or implemented are incremental in nature and hazard-specific. Yet, we demonstrate how action at earlier points in the framework could promise transformative adaptation, addressing the disconnection between people, place, and infrastructure in ways that incremental adaptation actions cannot.